call in design procedure (Journal of the College of Basic Education, 2022)
The design process has always been an emotional process in terms of the designer and the recipient, and had it not been for these emotions, the design idea would not have taken its rolling range in a world full of challenges, accelerating and renewable over time, which contributed to providing the atmosphere for the emergence of designs that often rise to the level of creativity, and the fact that the task of the interior designer requires From him direct contact with the problems and needs of the audience of recipients, so the need must necessitate him, so he generates an idea that makes him touch all the global material, technical, technological fields ... etc. in order to achieve it, which, as soon as it appears to the audience of recipients, it calls for their feelings of acceptance or rejection, announcing the birth of a design component Interaction between two main poles of the design process (the designer and the recipient).